1992
DOI: 10.1128/mcb.12.5.1977
|View full text |Cite
|
Sign up to set email alerts
|

A G-protein alpha subunit from asexual Candida albicans functions in the mating signal transduction pathway of Saccharomyces cerevisiae and is regulated by the a1-alpha 2 repressor.

Abstract: We have isolated a gene, designated CAG1, from Candida albicans by using the G-protein alpha-subunit clone SCG1 of Saccharomyces cerevisiae as a probe. Amino acid sequence comparison revealed that CAG1 is more homologous to SCG1 than to any other G protein reported so far. Homology between CAG1 and SCG1 not only includes the conserved guanine nucleotide binding domains but also spans the normally variable regions which are thought to be involved in interaction with the components of the specific signal transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 50 publications
(59 reference statements)
2
48
0
Order By: Relevance
“…Asterisks indicate residues implicated in the G ␣ -receptor interaction by the evolutionary trace method (33). Expression of C. albicans G ␣ gene CAG1 in an S. cerevisiae gpa1 mutant allowed mating (48), indicating that Cag1p can interact with the S. cerevisiae pheromone receptors. Most of the amino acid residues for which mutations resulted in mating defects altered residues conserved between Gpa1p and Cag1p.…”
Section: Strains Mutants Were Made By Using Isogenic Yeast Strains Wmentioning
confidence: 99%
“…Asterisks indicate residues implicated in the G ␣ -receptor interaction by the evolutionary trace method (33). Expression of C. albicans G ␣ gene CAG1 in an S. cerevisiae gpa1 mutant allowed mating (48), indicating that Cag1p can interact with the S. cerevisiae pheromone receptors. Most of the amino acid residues for which mutations resulted in mating defects altered residues conserved between Gpa1p and Cag1p.…”
Section: Strains Mutants Were Made By Using Isogenic Yeast Strains Wmentioning
confidence: 99%
“…Genetic or pharmacological manipulations of Nmt activity that reduce the fractional representation of N-myristoylated Arfs to this value would be expected to have a fungicidal effect. Other N-myristoylproteins are known to be produced by this organism, including a homologue of Gpalp encoded by the CAGl gene (Sadhu et al, 1992).…”
Section: Monitoring Protein N-myristoylation In Vivomentioning
confidence: 99%
“…Metabolic labeling studies indicate that this Nmt covalently attaches [ 3 H]myristate (C14:0) to the N-terminal Gly residues of fewer than 10 cellular proteins during exponential growth on rich media (5). These Nmt substrates include an ADP-ribosylation factor (Arf) (5,6) and Cga, a protein of unknown function that can complement the growth arrest and mating defects found in strains of Saccharomyces cerevisiae containing a null allele of its G protein ␣ subunit gene, GPA1 (7). Genetic studies have shown that Nmt is essential for viability.…”
mentioning
confidence: 99%